Aging, HIV infection, and alcohol exert synergist effects on regional thalamic volumes resulting in functional impairment - Adolf Pfefferbaum; Natalie M. Zahr; Stephanie A. Sassoon; Rosemary Fama; Manojkumar Saranathan; Kilian M. Pohl; Edith V. Sullivan (NeuroImage: Clinical)
Objective: Pharmacologically-treated people living with HIV infection have near-normal life spans with more than 50 % living into at-risk age for dementia and a disproportionate number relative to uninfected people engaging in unhealthy drinking. Accelerated aging in HIV occurs in some brain structures including the multinucleated thalamus. Unknown is whether aging with HIV affects thalamic nuclei and associated functions differentially and whether the common comorbidity of alcohol use disorder (AUD) + HIV accelerates aging. Methods: This mixed cross-sectional/longitudinal design examined 216 control, 69 HIV, and 74 HIV + AUD participants, age 25–75 years old at initial visit, examined 1–8 times. MRI thalamic volumetry, parcellated using THalamus Optimized Multi-Atlas Segmentation (THOMAS), identified 10 nuclei grouped into 4 functional regions for correlation with age and measures of neuropsychological, clinical, and hematological status. Results: Aging in the control group was best modeled with quadratic functions in the Anterior and Ventral regions and with linear functions in the Medial and Posterior regions. Relative to controls, age-related decline was even steeper in the Anterior and Ventral regions of the HIV group and in the Anterior region of the comorbid group. Anterior volumes of each HIV group declined significantly faster after age 50 (HIV = -2.4 %/year; HIV + AUD = -2.8 %/year) than that of controls (-1.8 %/year). Anterior and Ventral volumes were significantly smaller in the HIV + AUD than HIV-only group when controlling for infection factors. Although compared with controls HIV + AUD declined faster than HIV alone, the two HIV groups did not differ significantly from each other in aging rates. Declining Attention/Working Memory and Motor Skills performance correlated with Anterior and Posterior volume declines in the HIV + AUD group. Conclusions: Regional thalamic volumetry detected normal aging declines, differential and accelerated volume losses in HIV, relations between age-related nuclear and performance declines, and exacerbation of volume declines in comorbid AUD contributing to functional deficits.